PARTISIPASI MASYARAKAT DALAM MENGATASI PUTUS SEKOLAH DI KABUPATEN TANGERANG - Nia Qurrotul 'Ain (Jurnal Ilmu Pemerintahan, 2024)
Nia Qurrotul'ain, 6670190064, Citizens Participation in Overcoming School Dropouts in Tangerang, Dr. Elly Nurlia, M.Si., Government Science, Faculty of Social and Politic Science, Sultan Ageng Tirtayasa University, 2024. This article discusses community participation in overcoming school dropouts in the District. Tangerang. Tangerang Regency occupies the highest position in Banten Province regarding the number of children out of school. This makes the government in Kab. Tangerang solved the problem by creating a program and participating in the program. In this research, researchers used qualitative methods with a case study approach with community participation theory by Sherry Arnstein. The results of this research show that the Pakades Program is included in the moderate participation category where the community has the opportunity to convey their aspirations as material for consideration by the government in determining policy, but the community's authority to participate in formulating policy is not large. The role of the school committee is included in the high category where the community has influence on the decision-making process. Community participation (poor/vulnerable community groups) has entered the space for determining the process, results and impact of policies by implementing partnerships, namely that the community has been able to negotiate with "power holders." ” in an equal position, delegation of power means that the community has been able to direct policy because the decision-making space has been “controlled”.